Analisis Implementasi PPh 21 Non Pegawai Melalui e-Bupot 21 Dalam Pemadanan NIK-NPWP di PT ETA - Febi Pertiwi Riyanti Achmad; Fauzan Akbar Albastiah (CV. KAMPUS AKADEMIK PUBLISING, 2024)
PT ETA is a construction service company that also fulfills its tax obligations as a taxpayer, one of which is implementing the Income Tax Article 2 mechanism. Income Tax Article 21 is a type of tax that frequently undergoes refinements to facilitate its implementation. Through the Director General of Taxes Regulation Number PER-2/PJ/2024 and the integration of NIK-NPWP matching, it is expected to improve taxpayer compliance. This study aims to understand the calculation, withholding, and reporting mechanisms of Income Tax Article 21, analyze the compliance of its implementation, and prove that e-Bupot 21 can support the NIK-NPWP matching issue. The research method used is qualitative with a descriptive analysis approach through observation, interviews, and trials to objectively present the analysis results. The study results indicate that PT ETA has complied with the Director General of Taxes Regulation Number PER-2/PJ/2024 but violated Article 3 Paragraph 3 of the Republic of Indonesia Law Number 28 of 2007. Additionally, the implementation of NIK-NPWP matching in PMK 136 of 2023 has been well-executed in the 2024 tax year.